Implementation of Black Campaigns as a Form of Unfair Business Competition: A Review of the Fulfillment of the Elements of Article 1365 of the Civil Code: Implementasi Black Campaign Sebagai Bentuk Persaingan Usaha Tidak Sehat: Tinjauan Terhadap Pemenuhan Unsur-Unsur Pasal 1365 KUH Perdata - Britney Wilhelmina Berlian Mingga; Ariawan Gunadi (Academia Open, 2025)
General background: Indonesia’s rapid economic growth has intensified business competition, particularly through the increasing use of digital marketing strategies. Specific background: This environment has contributed to the rise of black campaign practices, which not only damage business reputations but also cause substantial material and immaterial losses, while regulatory clarity remains limited. Knowledge gap: Existing studies rarely examine black campaigns as a form of unfair business competition within the framework of unlawful acts under Article 1365 of the Indonesian Civil Code. Aim: This study analyzes whether black campaign practices fulfill the elements of an unlawful act—namely the existence of an act, illegality, fault, losses, and causal relationship—thereby establishing grounds for civil liability. Results: The findings demonstrate that the characteristics of black campaigns, including the dissemination of misleading information and direct attacks on competitors’ products and branding, substantively satisfy all elements of Article 1365. Novelty: This research highlights that black campaign disputes should not be viewed solely through the lens of criminal liability under the ITE Law, but can be more effectively resolved through civil liability mechanisms that address actual economic harm. Implications: The study underscores the importance of adopting civil law remedies to protect business continuity, market fairness, and economic stability within the digital competition landscape. Highlights: Black campaign practices meet all elements of unlawful acts under Article 1365. Civil liability offers a more effective remedy than relying solely on the ITE Law. Digital competition increases reputational and economic risks for businesses. Keywords: Black Campaign, Unfair Business Competition, Unlawful Act, Civil Liability, Digital Marketing